Ausstellungskommunikation : Eine linguistische Untersuchung multimodaler Wissenskommunikation im Raum - Kesselheim, Wolfgang (Berlin/Boston De Gruyter, 2021)
This study investigates museum exhibitions as multimodal communication offerings, of which texts and exhibits are just as much a part as exhibition architecture and design. It reconstructs the communicative potential of exhibitions from a text-linguistic and semiotic perspective before using conversation analysis to examine how visitors use exhibitions to construct knowledge about the exhibition topic.
Schweizerischer Nationalfonds zur Förderung der Wissenschaftlichen Forschung
German
Keywords: Language; linguistics; Semiotics / semiology; Multimodality; Interaction; Visitor Research